EXPLORING THE EFFECTS OF CPEC ON SOCIO-CULTURAL TRANSFORMATION IN PUNJAB, PAKISTAN - Sara Farooq; Muhammad Idrees; Naima Nawaz; Rao Sabir Sattar (International Journal of Contemporary Issues in Social Sciences, 2024)
CPEC, which stands for China-Pakistan Economic Corridor, is a mega project that combines both infrastructure and economic development. The project aims to connect the Gawadar Port in Pakistan with Xinjiang in China by building a network of highways, railways and pipelines. This is the signature undertaking under China’s mega BRI (Belt and Road Initiative), which seeks to maximize regional connectivity and China-Pakistan economic ties. The project is cross-sectored covering energy, transport, communication, and industries indiscriminately, underpinning the project’s comprehensiveness with far-reaching implications to both the participating countries and the wider region. China and Pakistan have agreed to build project more commonly known as China-Pakistan Economic Corridor (CPEC) is expected to bring about both peace and prosperity in South Asia. CPEC focused on improving the economy of both countries through social change in society. Culture is the way of living in society which includes both the tangible culture (buildings, technology etc.) and intangible culture (language, beliefs, ideas, knowledge and customs). When China and Pakistan collaborated with each other, their culture also diffused from one country to another. Because culture is an important part of society, we can’t separate both of them. This study aims to know about the perceptions and opinions of common people about the opportunities created through CPEC and its impacts on the socio-economic transformation of country. Cultural diversity affects positively or negatively the culture of native country. This socio-cultural transformation can lead to many social changes. The study was carried out in three districts of province Punjab, Sahiwal, Multan and Bahawalpur. These districts were selected purposively because the projects of CPEC were working so the data can be collected from those nearby areas. A sample of 480 respondents was selected randomly from three districts of selected regions of Punjab for getting quantitative data. Data was collected with the help of a well-structured Interview. Quantitative Data was analyzed through SPSS (statistical packages for social sciences). The major finding of the study suggested that the majority of the respondents agreed that CPEC gives better employment opportunities to the community. The majority of the respondents agreed that CPEC brings socio-economic transformation in all aspects of society like gender empowerment, language, culture, food, work ethics, security, GDP improvement and rural development. The partnership with Chinese firms on the project of CPEC is a vehicle for technology transfer, knowledge sharing, and innovation-driven growth in Punjab.